CAR T-cell therapies in China: rapid evolution and a bright future. Issue 12 (December 2022) - Hu, Yongxian; Feng, Jingjing; Gu, Tianning; Wang, Linqin; Wang, Yiyun; Zhou, Linghui; Hong, Ruimin; Tan Su Yin, Elaine; Zhang, Mingming; Lu, Peihua; Huang, He
Summary: Chimeric antigen receptor (CAR) T-cell therapies have achieved remarkable success in the treatment of haematological malignancies. Over the past 9 years, the use of CAR T-cell therapies has expanded throughout China, from the first clinical trials of CAR T cells conducted in 2013, to the world's largest number of CAR T-cell-related clinical trials in 2017, to a cumulative US$2·37 billion in funding for cell therapy companies in 2021, and a significant growth in the number of CAR T-cell-related clinical trials and basic research. This strong increase in activity is the result of a culmination of factors in China: strong government support, capital inflow, large patient demand, a unique health-care system, and the efforts of Chinese physicians and scientists. This Series paper provides an overview of the scope of CAR T-cell clinical trials in China (especially in the field of haematological malignancies), analyses the relevant policies, summarises the characteristics of corporate and capital support, and explores the achievements and challenges of CAR T-cell therapy in China to provide a better understanding for further promoting the development of cellular therapy and its clinical application.